1990
DOI: 10.1093/infdis/161.6.1302
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Vacuolization Caused by the Urease of Helicobacter pylori

Abstract: Tissue culture cells were exposed to supernatants of Helicobacter pylori for 24 h at 37 degrees C in the presence of various quantities of urea. In the normal human stomach the concentration of urea is less than or equal to 4 mmol/l, and in the presence of this low concentration up to 10% of Vero cells showed intracellular vacuolization. In the presence of 7.5 mmol/l urea, 25% of the cells showed vacuolization. With 30 mmol/l urea, the final pH was 7.6, indicating that vacuolization was not due to change of pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 10 publications
1
32
0
Order By: Relevance
“…pylori cytotoxicity only when the urea content of the cell incubation medium is in the range found for the human gastric juice. If this requirement is fulfilled, the large amounts of ammonia produced by bacterial urease greatly damage epithelial cells, as previously suggested by several investigations [21,25,29,30,37], It is well known that in vivo, gastric ammonia production is exclusively bacterial and that it is proportional to the amount of urea diffusing from blood to gastric juice. Hazell et al [38] dem onstrated that the urease activity of H. pylori is predictive of its virulence, and proposed that ammonia produced via the urease-dependent pathway may be cytotoxic to the mucosa [39].…”
Section: Discussionmentioning
confidence: 83%
“…pylori cytotoxicity only when the urea content of the cell incubation medium is in the range found for the human gastric juice. If this requirement is fulfilled, the large amounts of ammonia produced by bacterial urease greatly damage epithelial cells, as previously suggested by several investigations [21,25,29,30,37], It is well known that in vivo, gastric ammonia production is exclusively bacterial and that it is proportional to the amount of urea diffusing from blood to gastric juice. Hazell et al [38] dem onstrated that the urease activity of H. pylori is predictive of its virulence, and proposed that ammonia produced via the urease-dependent pathway may be cytotoxic to the mucosa [39].…”
Section: Discussionmentioning
confidence: 83%
“…Although there is no report about higher level of urease activity in patients with peptic ulcer, the increased activity was previously established in strains from cancer patients (Ito et al, 1995). In a study by Xu et al (1990) it was shown that urease inhibitor can cause a 75% drop in vacuolating gastric cells that had been induced by defined concentration of urease. While our results showed higher activity of this enzyme in the strains collected from ulcerative tissue, it remains to clarify its effect on gastric acid secretion and ulcer formation in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to pathogenicity from H. pylori, evidence indicates that ammonia generated by urease can cause injury to the gastroduodenal mucosa (33,42). Specific inhibition of urease activity has been proposed as a possible strategy to inhibit this microorganism (25).…”
mentioning
confidence: 99%